The Impact of Permissive Parenting on Children's Character Development - Siti Maghfirah; Ocha Arrifa Lyanda (Inovan Publisher, 2025)
The aim of this research is to determine parents' permissive parenting patterns on early childhood character development. Parents are the main source of education and an important model who plays a role in a child's growth and development. There are several important aspects that must be considered as goals for achieving child development. This can be achieved if parents implement appropriate parenting patterns for the child's growth and development. Parenting style can be interpreted as a way of implementing it in guiding, directing and even managing a child's growth and development. Appropriate and appropriate parenting patterns will definitely stimulate children's development well and optimally. Therefore, the researcher intends to find out the impact of permissive parenting on the development of children's character by parents. Through the permissive parenting style carried out by parents, it has an impact on development child is that children never learn to control their own behavior and always expect to get their way.